2016
DOI: 10.1039/c6ra20131h
|View full text |Cite|
|
Sign up to set email alerts
|

Self-assembly of silicon/carbon hybrids and natural graphite as anode materials for lithium-ion batteries

Abstract: Si–C–NG composites exhibit a high specific capacity, a high initial coulombic efficiency, and a good cycling stability with capacity retention after 100 cycles at a current density of 100 mA g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Mixing multiple polymers as carbon precursors is also one of the rational strategies for developing carbonaceous additives. Wang et al 84 reported a Si-C-NG composite, where NG is natural graphite, with two polymers-poly (acrylonitrile-co-divinylbenzene) (denoted as Si/poly(ANco-DVB)) synthesized through ball milling, spray drying, and subsequent pyrolysis (Figure 7B and 7C). Through microsuspension polymerization, nano-Si was well encapsulated in chemically cross-linked poly(AN-co-DVB) microspheres, which could effectively restrict the agglomeration of Si and strengthen the bonding between Si and graphite via the conjugated carbon backbone from the pyrolysis of poly(AN-co-DVB).…”
Section: Other Polymer-derived Carbonmentioning
confidence: 99%
“…Mixing multiple polymers as carbon precursors is also one of the rational strategies for developing carbonaceous additives. Wang et al 84 reported a Si-C-NG composite, where NG is natural graphite, with two polymers-poly (acrylonitrile-co-divinylbenzene) (denoted as Si/poly(ANco-DVB)) synthesized through ball milling, spray drying, and subsequent pyrolysis (Figure 7B and 7C). Through microsuspension polymerization, nano-Si was well encapsulated in chemically cross-linked poly(AN-co-DVB) microspheres, which could effectively restrict the agglomeration of Si and strengthen the bonding between Si and graphite via the conjugated carbon backbone from the pyrolysis of poly(AN-co-DVB).…”
Section: Other Polymer-derived Carbonmentioning
confidence: 99%
“…The peaks at 2 θ = 26.5° and 54.5° of EG correspond to lattice planes of (002) and (004), respectively. The peak at 54.5° is ascribed to the incomplete oxidation of the graphite basal plane, 32 whereas the peak at 2 θ = 26.5° corresponds to the lattice plane (002). This may be due to the presence of GNSs sidewall in EG stack.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 44.2° represents NGF and peak at 54.5° may be due to the incomplete oxidation of the graphitic basal plane. 17 The interlayer distance between graphitic layers can be calculated by Bragg’s relation: nλ = 2 d sin θ , where λ is X-ray wavelength of 0.154 nm, d is inter planer spacing, and θ is Bragg’s angle. Corresponding to the strong diffraction peak at 26.6°, the “ d ” planner spacing of graphitic layers or graphene nanosheets is found to be 0.336 nm.…”
Section: Resultsmentioning
confidence: 99%